2024
DOI: 10.3390/diagnostics14040405
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with Wearable Sensors in Oncology during Treatment: Lessons Learned from Feasibility Research Projects in Denmark

Helle Pappot,
Emma Balch Steen-Olsen,
Cecilie Holländer-Mieritz

Abstract: Background: The fraction of elderly people in the population is growing, the incidence of some cancers is increasing, and the number of available cancer treatments is evolving, causing a challenge to healthcare systems. New healthcare tools are needed, and wearable sensors could partly be potential solutions. The aim of this case report is to describe the Danish research experience with wearable sensors in oncology reporting from three oncological wearable research projects. Case studies: Three planned case st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Through innovative weaving techniques, long-sized ECLCC fibers were seamlessly integrated into textiles, opening up a plethora of possibilities for wearable flexible displays. Celina Jones et al reported on a solution for inkjet printing of CLC onto hydrophobically pretreated textiles as an alternative to existing chemical dyeing techniques [ 207 ]. The resulting colored films showed a greater degree of color than those on untreated textiles.…”
Section: Advanced Optical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through innovative weaving techniques, long-sized ECLCC fibers were seamlessly integrated into textiles, opening up a plethora of possibilities for wearable flexible displays. Celina Jones et al reported on a solution for inkjet printing of CLC onto hydrophobically pretreated textiles as an alternative to existing chemical dyeing techniques [ 207 ]. The resulting colored films showed a greater degree of color than those on untreated textiles.…”
Section: Advanced Optical Applicationsmentioning
confidence: 99%
“… Smart wearable fabrics and devices. ( a ) Structural color response of smart CLC fibers to strain, temperature, and electrical signals [ 205 , 206 , 207 ]. ( b ) Wearable CLC fabrics and devices: clothing, bandages, belts, and gloves can detect sweat, temperature, and pressure [ 208 ].…”
Section: Figurementioning
confidence: 99%